Crystal structure, thermal behavior and spectroscopic studies of a new organic hydrogen arsenate (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
The present paper undertakes the study of a title organic-inorganic hybrid material 2-amino-3-benzyloxy pyridinium dihydrogenmonoarsenate, [C12H13N2O]H2AsO4, which has been synthesized by slow evaporation at room temperature using 2-amino-3-benzyloxypyridine as the structure-directing agent. The structure was determined by single-crystal X-ray diffraction at 296 K. This compound is crystallized in the noncentrosymmetric orthorhombic space group P212121 with the lattice parameters a = 4.89 (7), b = 10.41 (1), c = 26.79 (3) Ã…, V = 1364.3 (3) Ã…3, and Z = 4. The crystal structure has been determined and refined to R1 = 0.0363 and wR2 = 0.1246 using 5438 independent reflections. The atomic arrangement can be described by infinite anionic chains running parallel to the [100] direction. The organic entities are located between these chains. H-bonds connecting the different species play an important role in the one-dimensional network cohesion. This compound is also characterized by solid-state 13C MAS NMR, IR, Raman spectroscopy and TG-ATD thermal analysis. Moreover, protonic conduction of this compound determined by impedance has been studied in the temperature range 299 - 403 K.